Investigating brand community engagement and evangelistic tendencies on social media. Issue 1 (22nd February 2021) - Sharma, Purvendu; Sadh, Ashish; Billore, Aditya; Motiani, Manoj
Abstract : Purpose: This study aims to explore the antecedents and outcomes of brand community engagement (BCE) in the context of social media-based brand communities (SMBCs). Moreover, the mediating role of brand evangelism between BCE and brand defence and between BCE and brand resilience is examined. Design/methodology/approach: The data was collected using a questionnaire-based survey from 201 active members of various SMBCs. Partial least square based structural equation modelling is used to test the proposed conceptual model. Findings: The results suggest that brand identification and brand prominence are the antecedents of BCE. BCE positively influence brand evangelism and brand defence. Furthermore, the finding suggests that brand evangelism mediates the relationship between BCE and brand defence and also between BCE and brand resilience. Research limitations/implications: The sample for this study involves respondents active on different SMBCs, which may constrain uniformity in respondents' experiences. Practical implications: The insights provided by this study are useful in enhancing BCE with the SMBCs. The study highlights the role of brand evangelism in actively endorsing and defending the brands. The brand manager can promote brand evangelistic behaviour through meaningful engagement with SMBCs. Originality/value: The study contributes to the literature of brand community engagement by focussing on its antecedents and outcomes in SMBCs. Further, this study adds to the branding literature by connecting two crucial streams of brand research: BCE and brand evangelism. The study also explores the mediating role of brand evangelism. It enhances the understanding of consumer-brand relationships in the context of SMBCs.